On some basic character of differentiation in neutrosophic normed spaces - Khan, Vakeel A.; Khan, Mohammad Daud; Arshad, Mohammad; Et, Mikail (Univ Nis, Fac Sci Math, 2025)
In this presented article, we have exemplified and studied the Frechet differentiation of nonlinear operators between neutrosophic normed spaces as a generalization of notions given [34] and introduced nonlinear theory of neutrosophic bounded operators by introducing chain rule and some algebraic properties of Frechet differentiation of operators between neutrosophic normed spaces.
Keywords: Bounded linear operator; Frechet derivative; continuity; chain rule; neutrosophic normed space